Synthesis And Characterization Of Mil-101(Cr) And Zno@mil-101(Cr) For Photocatalytic Degradation Of Phenanthrene - Adamu, Usman Abubakar (2024)
In this study, a low-temperature hydrothermal method was employed to prepare highly porous and well-defined MIL-101(Cr) metal-organic frameworks. A series of chromium-based MOFs (MIL-101) was synthesized at different temperatures: 150, 160, 170, 180, 200, and 220 ºC. The synthesized MOFs were characterized using various techniques. The effectiveness of these synthesized photocatalysts was assessed for the photocatalytic degradation of phenanthrene (PHE) under UV light exposure. Remarkably, 98% degradation of PHE was obtained within 150 minutes of UV light irradiation with MIL-101@160 under specific optimized conditions, which included a PHE concentration of 2 ppm, pH 7, and a catalyst dosage of 30 mg. The enhanced degradation efficiency of MIL-101@160 could be attributed to its high specific surface area and thermal stability. ZnO was synthesized through a biosynthesis method and subsequently utilized to fabricate ZnO@MIL-101(Cr) nanocomposites, with preparation carried out at temperatures of 160 ºC and 220 ºC, respectively. These catalysts were characterized using fourier tranform infrared, X-ray diffraction, Scanning Electron Microscopy, X-ray Photoelectron Spectroscopy, ultraviolet-visible diffuse reflectance spectroscopy, and photoluminescence analyses, The effectiveness of the ZnO@MIL-101(Cr) nanocomposite in photocatalysis was evaluated for the degradation of PHE, utilizing both UV and visible light irradiation. The effect of different parameters such as solution pH, catalyst loading, the source of light, catalyst reusability, and the effect of temperature on PHE degradation were evaluated.